Reinvigorating Growth in Belize - Vasilyev, Dmitry (IMF Working Papers; Working Paper ;, 2019)
In the 1990s and early 2000s, Belize grew faster than its regional peers. By the mid-2000s, however, economic growth had slowed down to the regional average. A vicious circle of low growth and increasing public debt has been clouding Belize's outlook. This paper applies a growth diagnostic approach based on the Hausmann-Rodrik-Velasco framework to investigate the main growth constraints and opportunities for higher growth in Belize. Improvements in access to finance and in the business climate could unlock Belize's strengths.